A generalization of the fatigue Kohout-Věchet model for several fatigue damage parameters. (November 2017) - Correia, J.A.F.O.; Raposo, P.; Muniz-Calvente, M.; Blasón, S.; Lesiuk, G.; De Jesus, A.M.P.; Moreira, P.M.G.P.; Calçada, R.A.B.; Canteli, A.F.
Highlights: A new generalization of the Kohout-Věchet (KV) fatigue model is proposed. Stress, Strain and Energy-based fatigue damage variables are used. Full range of fatigue lives covered from quasi-static to VHCF. Proposal verified for existing data for P355NL1 steel and a Puddle Iron. Abstract: A new proposal of generalization of the fatigue Kohout-Věchet (KV) model for different fatigue damage parameters is proposed. The purpose of this generalized model is to describe all fatigue regimes from very low-cycle fatigue (VLCF) to very high-cycle fatigue (VHCF), and accounting for several fatigue damage parameters, such as, strain parameter, Smith-Watson-Topper (SWT) parameter, Walker-like strain parameter, energy-based parameter in uniaxial loading conditions, among others. The full range of fatigue life responses for all loading regimes of materials and structural components are extremely important in the fatigue design. Engineering structures are subjected to different types of loading that cause fatigue failure. These loadings can range from quasi-static monotonic loading to long term dynamic/cyclic loading. In this paper, a proposal of generalization of the KV model for several fatigue damage parameters was verified and compared with experimental fatigue results under uniaxial loading conditions available in literature. This study validates the importance and applicability of full range fatigue life models for different damage parameters in fatigue life prediction of materials and structural components.